Structured Display and Browsing of Documentary Information: VIBE in Action - Korfhage, Robert R.; Parmanto, Bambang (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Traditional information retrieval systems present the user with a very limited view of the document database, erecting a barrier to information at the same time as supplying the user with information. In this paper we present a graphical interface, VIBE, designed to eliminate this barrier and present the user with more complete access to information